Pengaruh Motivasi Terhadap Kedisiplinan Masyarakat Dalam Membayar Pajak Bumi dan Bangunan (PBB) di Kelurahan Dawuhan Kecamatan Situbondo Kabupaten Situbondo - Hasan Muchtar Fauzi; Fridasanti Dwi Kismadani (ACTON, 2019)
Motivation is a very important thing to be considered by the company if you want every employee to contribute positively to the achievement of company goals, because with the motivation of an employee will have a high enthusiasm in carrying out their duties and responsibilities. Tax revenue is a source of funds to improve progress and prosperity in society, including providing opportunities for poor people to improve their standard of living. From these uses it can be seen that the tax contains elements of equity and justice . The formulation of the problem in this research is whether there is a motivational effect on the discipline of the community in paying land and building tax (PBB) in Dawuhan Village, Situbondo District, Situbondo Regency. The research method uses quantitative research, with a survey approach that is research that takes samples from the population and uses a questionnaire as a primary data collection tool . The results of the analysis conducted by researchers found that the t-test value of 8.753> 1.984 table. Based on the significance value, it can be concluded that the significance value of 0,000 is below 0.05 which means that Ho is rejected and Ha is accepted, this shows that there is a motivational effect on the discipline of the community in paying land and building tax (PBB) in Dawuhan Sub-District, Situbondo, Situbondo Regency .